2010
DOI: 10.1007/s10048-010-0241-x
|View full text |Cite
|
Sign up to set email alerts
|

LINGO1 and LINGO2 variants are associated with essential tremor and Parkinson disease

Abstract: Genetic variation in the leucine-rich repeat and Ig domain containing 1 gene (LINGO1) was recently associated with an increased risk of developing essential tremor (ET) and Parkinson disease (PD). Herein, we performed a comprehensive study of LINGO1 and its paralog LINGO2 in ET and PD by sequencing both genes in patients (ET, n=95; PD, n=96) and by examining haplotype-tagging single-nucleotide polymorphisms (tSNPs) in a multicenter North American series of patients (ET, n=1,247; PD, n=633) and controls (n=642)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
126
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(133 citation statements)
references
References 30 publications
5
126
0
2
Order By: Relevance
“…6 This finding was confirmed by several but not all other groups attempting replication. [7][8][9] Here, we present the second GWAS for ET.…”
mentioning
confidence: 99%
“…6 This finding was confirmed by several but not all other groups attempting replication. [7][8][9] Here, we present the second GWAS for ET.…”
mentioning
confidence: 99%
“…In addition, using the RegulomeDB website, rs10813121 in chromosome 9 was found to bind to seven proteins, among them STAT3 and Nrf-2, a key transcription factor that regulates antioxidant defense in macrophages and epithelial cells (35). The leucine-rich repeat and Ig domaincontaining 2 gene (LINGO2) is expressed in neuronal tissue, and variants have been associated with essential tremor and Parkinson's disease as well as obesity (36)(37)(38). The function of LINGO2 is currently unclear, and further investigation is needed to understand its potential role in the pathogenesis of airway responsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…A large genome-wide association study has shown that the "leucine-rich repeat (LRR) and immunoglobulin (lg) domaincontaining, Nogo receptor-interacting protein-I (LINGO 1) gene" which has a role in pathogenesis of essential tremor could be equally be associated with PD [216].…”
Section: Llngo1 and Llngo2mentioning
confidence: 99%